Environment Parameters Control Based on Wireless Sensor Network in Livestock Buildings - Yu Zhang; Qiyu Chen; Guanting Liu; Weizheng Shen; Guanlin Wang (International Journal of Distributed Sensor Networks)
The products quality and welfare of animals are closely related to the environment parameters in livestock buildings. A monitoring and control method of environment parameters in livestock buildings based on wireless sensor network is proposed in this paper. Temperature, humidity, light, carbon dioxide concentration, ammonia concentration, and hydrogen sulfide concentration can be monitored in real time by this method. The above six parameters will be adjusted and controlled through WLS algorithm and the minimizing deviation criteria. Compared with the traditional method, the high labor cost will be saved and energy consumption will be decreased. The experimental results show that this method can in real time monitor, effectively adjust, and control the environmental parameters in livestock buildings.